GENDER PERSPECTIVE AND TRIALS BY JURIES: THE MECHANISMS OF CONTROL OF BIRTHS AND GENDER STEREOTYPES IN TRIAL BY JURIES - VILLANUEVA, CARLOS MARTIN; STAMILE, NATALINA (Constituição, Economia e Desenvolvimento: Revista Eletrônica da Academia Brasileira de Direito Constitucional, 2021)
One of the aims of this paper is to analyze the mechanisms for controlling stereotypes and implicit gender biases in trial by jury in Argentina. Especially, we will focus on the results achieved regarding the existence of gender biases and stereotypes when exercising the jurisdictional function, as well as in the description of the control systems over them, and the measures that could be carried out to better face this kind of stereotypes and biases within this institution.